Ensuring the Right to Education for Roma Children: an Anglo-Swedish Perspective. (22nd May 2017) - Harris, Neville; Ryffé, David; Scullion, Lisa; Stendahl, Sara
ABSTRACT: Access to public education systems has tended to be below normative levels where Roma children are concerned. Various long-standing social, cultural, and institutional factors lie behind the lower levels of engagement and achievement of Roma children in education, relative to many others, which is reflective of the general lack of integration of their families in mainstream society. The risks to Roma children's educational interests are well recognized internationally, particularly at the European level. They have prompted a range of policy initiatives and legal instruments to protect rights and promote equality and inclusion, on top of the framework of international human rights and minority protections. Nevertheless, states' autonomy in tailoring educational arrangements to their budgets and national policy agendas has contributed to considerable international variation in specific provision for Roma children. As this article discusses, even between two socially liberal countries, the UK and Sweden, with their well-advanced welfare states and public systems of social support, there is a divergence in protection, one which underlines the need for a more consistent and positive approach to upholding the education rights and interests of children in this most marginalized and often discriminated against minority group.